Harnessing Renewable Energy at Kalasalingam Academy of Research and Education – A Role Model Case - T.R., Neelakandan; V, Pandiyarajan; Sridharan, Shasi Anand; Ramrao, Nagaraj (Universitas Diponegoro, 2021)
Global energy demand and environmental concerns are the driving force for the use of alternative sustainable and ecofriendly renewable energy sources. Solar energy is the inexhaustible and CO2 emission free energy source worldwide. It produces significant environmental benefits in comparison to the conventional energy sources, thus contributing to the sustainable development of human activities. It produces clean and renewable power from the sun and benefits the environment without causing air and water pollution. Alternatives to fossil fuels reduce carbon foot print across the globe reducing emission of greenhouse gases and become ecofriendly. Solar power has attracted the largest share of new investments in solar energy across the world. This research article shows light on the solar energy sources developed by Kalasalingam Academy of Research and Education (KARE) for the effective utilization of solar energy in the campus and its impact on the reduction in carbon foot print and also the impact of green vegetation as a source of carbon sink for an ecofriendly campus.